PENGARUH TEKANAN DAN TEMPERATUR TERHADAP LAJU MASSA PADA SIKLUS RANKIN ORGANIK SEDERHANA - Achmad Husein Siregar; Andi Pintoro (Jurnal Simetri Rekayasa, 2019)
Electricity is a major need for people, especially in Indonesia. The need for electricity is increasing every year. In 2019 PLN estimates that electricity consumption will grow by 6%. To meet the demand for electricity supply and in particular to provide renewable and environmentally friendly electricity, a breakthrough is needed in the search for new and renewable sources of electricity. One of them is the potential source of electrical energy from geothermal heat sources, especially those of low quality. In this research an experimental study was carried out on a laboratory-scale power generation system with the principle of a simple Organic Rankine Cycle with a low-quality geothermal heat source. The generator system is designed, then built and finally tested using R134a as a working fluid. The main components of this system are the vane pump (to increase working fluid pressure), evaporator (to absorb heat from heat sources), expanders / turbines (to convert heat energy into kinetic energy) and condenser (to convert the phase of working fluid into saturated liquid). In this study, we will look for the influence of variations in pressure and temperature on the mass flow rate of the working fluid which is one of the factors that determine the performance of the observed system. In this experiment, it was concluded that by maintaining a constant temperature and increasing evaporation pressure, a mass flow rate would decrease. Constant temperature is carried out at 80 oC, 85 oC, 90 oC, 95 oC and 100 oC. A decrease in the mass flow rate when the pressure is raised at a constant temperature will result in better system performance.